2010
DOI: 10.1007/s10722-009-9506-3
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analyses for evaluation of genetic diversity among Sicilian grapevine cultivars

Abstract: A total of 82 grapevine genotypes were sampled from several areas of the Italian region of Sicily where vineyards are widely spread. The grapevines were characterized using six microsatellite markers (VVS2, VVMD5, VVMD7, VVMD27, VrZAG62 and VrZAG79) to evaluate genetic diversity. Thirty-seven of the 82 cultivars sampled had their names quoted in historical and literary sources, while 45 cultivars from old vineyards did not have their names reported in ancient literature. According to their genetic profiles at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
5
25
2
Order By: Relevance
“…While we found commonalities with Carimi et al (2010) (Catarratto, Diretta bianca, Inzolia, Lacrime i Maria, Rucignola and Zibibbo), but none with De Lorenzis et al (2014), the vast majority (69 out of 75) of the varieties found in the circum-Sicilian minor islands were not reported until now in mainland Sicily. This study confirms that the minor islands of the Mediterranean Basin still represent underexplored hotspots of genetic diversity for grapevine.…”
Section: Discussioncontrasting
confidence: 70%
“…While we found commonalities with Carimi et al (2010) (Catarratto, Diretta bianca, Inzolia, Lacrime i Maria, Rucignola and Zibibbo), but none with De Lorenzis et al (2014), the vast majority (69 out of 75) of the varieties found in the circum-Sicilian minor islands were not reported until now in mainland Sicily. This study confirms that the minor islands of the Mediterranean Basin still represent underexplored hotspots of genetic diversity for grapevine.…”
Section: Discussioncontrasting
confidence: 70%
“…Since the Vitis18kSNP array contains about 25 % of loci identified from different Vitis species (V. aestivalis, V. berlandierii, V. labrusca, V. cinerea, V. lincecumi, and Muscadinia rotundifolia), the percentage of SNP loci (3 %) showing any fragment amplification appeared reasonable, as compared to previous reports (Bekele et al 2013;De Lorenzis et al 2015). The percentage of polymorphic loci was high, and the values of heterozygosity (expected, H e and observed, H o ), very similar among them, lower than those reported for Sicilian collections analyzed by SSR markers (Carimi et al 2010;De Lorenzis et al 2014). These results are expected due to the bi-allelic nature of SNPs, although the higher discriminating powerful through the larger number of loci analyzed.…”
Section: Discussionsupporting
confidence: 42%
“…plantnet-project.org). In the context of the clonal selection program in Sicily, the genetic variability among the main cultivars was assessed based also on selected SSR panel (Carimi et al 2010(Carimi et al , 2011De Lorenzis et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The long history of cultivation has led to a high number of autochthonous grapevine varieties, which represents an important source of genetic diversity. Accordingly, Sicilian varieties are characterized by high variability (Carimi et al 2010), having been subjected to mass selection by growers for centuries.…”
Section: Introductionmentioning
confidence: 99%